Thermal degradation kinetics of bioflavonoids from Orthosiphon stamineus - Lau, Siaw Jing (2013)
Orthosiphon stamineus which also known as Misai Kucing are traditional used for improve general health and treatment of disease.However,degradation of bioflavonoids occurred and the nutritional value of the final product decrease while product processing and storage.The objectives of this research are to determine the suitable solvent for Orthosiphon stamineus extraction and to elucidate the thermal degradation kinetics of bioflavonoids content from Orthosiphon stamineus using Hinrichs-Rademacher and Arrhenius equation to obtain the kinetic parameters.The research focused on experimenting different solvent type for the extraction and thermal degradation of bioflavonoids Orthosiphon stamineus which analyzed by UPLC and UV-Vis Spectrophotometer.The experiment will be conducted to find the degradation pattern for 60, 90 and 120°C and 0, 6, 12, 18, 23, 33 minutes.Then,model the results with Hinrichs-Rademacher degradation kinetics approach and Arrhenius equation.The result of solvent extraction showed the suitable solvent used was 70% methanol.The active components showed degraded while temperature and residence time increased.Eupatorin showed larger degradation while Rosmarinic Acid and Sinensetin showed less degradation.The experiment data obtained showed fitted well by both equation using Microsoft Excel Solver and degradation rate constant showed increasing while heating temperature and residence time increased.